FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI DI WILAYAH KERJA PUSKESMAS SENAPELAN KOTA PEKANBARU TAHUN 2016 - Rasyid, Zulmeliza; Megawati, Astria (Sistem Informasi, 2016)
Exclusive breastfeeding is the only baby only breast-fed for 6 months without any additional fluid, such as formula milk, orange juice, honey, tea, water and without supplementary feeding others, such as banana, milk porridge, biscuits, porridge or rice porridge. Scope of exclusive breastfeeding in Senapelan work area health center in 2015 is 56 %. Scope of exclusive breastfeeding in 2015 decreased from 2014 the amount of coverage is at 57.44 %This research method is analytic quantitative of observational with cross sectional design. This research sample counted 90 respondents. Technique intake of sample is proportional sampling and data collection do with interviewing mothers with babies aged 7-11 months using questionnaires. Analysis the used are analysis univariate, bivariate analysis with Chi - Square test and multivariate and data processing using computerized. Results of research show there are correlation between motherâs knowledge (Pvalue = 0,0001 , value of POR = 10,094 ) , motherâs education (Pvalue = 0,013, value of POR = 3,421 ) , mothers work ( Pvalue = 0,025 , value of POR = 3,058), motherâs habits ( Pvalue = 0,0001, value of POR = 15,600) and the role of health workers ( Pvalue = 0,0001, value of POR = 13,388 ) with exclusive breastfeeding for the baby. Suggested for holders need to improve outreach programs and socialization for mothers, the general public, working mothers, either in health centers, integrated service post and in classes pregnant women about the importance of exclusive breastfeeding in infants. And to the mother who has a baby to be more diligent in bringing babies to integrated service post Health Services as well as searching for information on exclusive breastfeeding.